Televised Political Learning: Influence of Prime-Time Televised Political News and Debates on the Political Awareness of the Viewers of Malayalam TV News Channels - Abdul Muneer V (International Journal of Humanities and Social Science Invention, 2014)
Despite the emergence of a series of news channels in India in the past few decades, the influence of news shows on public opinion has hardly been studied in the country. Given the size, reach and popularity they enjoy in Malayalam, news channels in Kerala can match any of their counterparts in the advanced world. Yet, few researches have been done to map their influence on the masses. Using data from a before-and-after panel survey conducted during the 2011 Kerala Assembly polls campaign, primarily aimed to assess the influence of election news and debates on the voting behaviour of viewers of Malayalam TV news channels, this study examines how prime-time televised political news and debates influence political awareness of viewers of Malayalam TV news channels during an election campaign. Analysing the responses of 512 voters in Kerala (N = 512), gathered through the first-wave pre-campaign survey, the study shows high viewership of political news and debates helps enhance viewers' political awareness. The study has found that sampled respondents as a whole had an appreciably high mean score of little more than 15. Further, it suggests that all socio demographic variables except economic status had a significant bearing on the viewers' political awareness. While high levels of political awareness was more salient among male, the upper-aged, highly educated, and employees in government and private sectors, it was low among females, homemakers and students.